Claremont Colleges Emergency Preparedness: An Action Research Initiative - Raman, Murali (2006)
This study examines the role of knowledge management systems in the context of emergency preparedness at Claremont University Consortium. The research objectives required the researcher's direct involvement with CUC. Canonical action research methodology was used to guide the project. Overall, the client was satisfied with the project's outcome. The researcher designed and implemented an instantiation of a web-based knowledge management system using Wiki technology. This system can assist CUC in overcoming some of its immediate concerns with emergency preparedness. These include the ability of the system to facilitate the communication process, and enable a more structured approach for documenting and storing emergency related information. The system as it exists today is subject to further improvement. This includes the need for continuous training with the system, improving the navigational aspects, and seeking a better fit between the system and the emergency planning and response processes.